Stability, Prognostic Factors and Survival of Spinal Bone Metastases in Malignant Melanoma Patients after Palliative Radiotherapy. Issue 2 (March 2016) - Bostel, Tilman; Förster, Robert; Schlampp, Ingmar; Wolf, Robert; Serras, Andre Franke; Mayer, Arnulf; Bruckner, Thomas; Welzel, Thomas; Schmidberger, Heinz; Debus, Jürgen; Rief, Harald
Purpose: This retrospective analysis aimed to evaluate the stability of spinal metastases in malignant melanoma patients following radiotherapy (RT), and to assess prognostic factors for survival. Methods: Forty-one patients with malignant melanoma and osteolytic spinal bone metastases were irradiated at the university clinics of Heidelberg and Mainz between July 2003 and October 2013. Three and six months after palliative RT, only 20 and 15 patients, respectively, were still alive and were therefore assessed for spinal stability using the Taneichi score based on CT imaging. Additionally, overall survival (OS) and bone survival (BS) rates as well as prognostic factors for BS were evaluated for all study patients. Results: Before RT, 19 patients (46.3%) were rated unstable. In the surviving patients, none of the unstable metastases were classified as stable 6 months after RT. Five-year OS was 23.3% and median BS was 4 months (range 0.5-29.8). Accordingly, only 36.6% of the patients were still alive 6 months after RT. Karnofsky performance score (KPS) <70%, visceral metastases and more than one bone metastasis were significantly predictive of poor BS. Conclusions: Our study population was characterized by poor BS and a lack of benefit with regard to stabilization of initially unstable spinal bone metastases 3 and 6 months after RT. This applies in particular to patients with a KPS <70%, visceral metastases and multiple bone metastases. Given the limited life expectancy, short fractionated treatment schedules of RT may be preferred in this population.